Principles and Practice of Urooncology : Radiotherapy, Surgery and Systemic Therapy - Ozyigit, Gokhan; Selek, Ugur (Springer International Publishing : Imprint: Springer, 2017)
This evidence-based, state of the art guide to the management of urological malignancies, including bladder cancer, prostate cancer, and testicular cancer, is designed to serve as an easy-to-consult reference that will assist in daily decision making and the delivery of optimal care for individual patients within a multidisciplinary setting. Readers will find up-to-date information on patient selection and the full range of treatment modalities, including modern radiotherapy techniques, systemic chemotherapy, surgical procedures (including robotic surgery and other minimally invasive approaches), hormonal therapies, immunotherapy, and focal therapies. With regard to radiotherapy, the coverage encompasses everything from delineation of tumor volumes and organs at risk based on CT simulation through to delivery of stereotactic body radiotherapy, intensity-modulated radiation therapy, tomotherapy, volumetric modulated arc therapy, and proton therapy. The authors are leading authorities with international reputations who have been selected for their expertise in the topic that they address. The book will be of value for all practicing urooncologists as well as other oncology fellows and residents interested in urooncology.
Keywords: Medicine.; Radiotherapy.; Oncology.; Urology.; elektronické knihy; electronic books